The Sublime Hope for Death: The Metathanatic Elocutio in Poema (1958) by Carlos Germán Belli - Sánchez Martínez, César Félix (2022)
When studying elocutio in Poema, a poetry piece by Carlos Germán Belli, expressed in numerous linguistic écarts so peculiar that many have signaled its ‘strange condition’, it can be found a spiritual etymology associated with Classical philosophical tradition in expression as well as in content, and also in all linguistic dimensions. Such a link reveals the poem as a consummated totality, in which an absolute correspondence exists between linguistic expression and metaphysical sense.